Leiomyoma cellulare in the broad ligament of the uterus - L. Sikora-Szczęśniak, Dobrosława (Menopause Review/Przegląd Menopauzalny, 2018)
There are only two reports on leiomyoma cellulare (LC) in the parametrium that have been published so far. Aim of the study was analysis of two cases of LC in the parametrium diagnosed postoperatively, and review of literature on the subject. Case 1: A 50-year-old patient was operated on for LC located in the right parametrium and concomitant malignant tumour in the right ovary. Leiomyoma cellulare was resected, hysterectomy and bilateral appendectomy performed, and bilateral iliac and obturator lymph nodes excised. Case 2: A 46-year-old patient was operated on for giant LC, on the left side, reaching the retroperitoneal space in the meso- and epigastrium. Leiomyoma cellulare was resected, and hysterectomy and bilateral appendectomy performed. The patient was reoperated twice due to haemorrhage within 24 hours following the operation. A literature review found reports on two cases of LC in 29- and 50-year-old patients with LC in the parametrium, located on the right and left side, respectively. Casuistic location of LC in the parametrium justifies reporting the cases in the literature. Preoperative diagnosis of LC in the parametrium is difficult. Conservative treatment, i.e. myomectomy should be reserved for those patients who wish to maintain fertility.